Assessing the potential impact of avian influenza on poultry in West Africa: A spatial equilibrium model analysis - You, Liangzhi; Diao, Xinshen (Wiley, 2007)
We analyse the potential economic impacts of avian influenza (AI) in Nigeria, using a spatial equilibrium simulation model. Depending on the size of the affected areas, the direct impact of the spread of AI along the two major migratory bird flyways would be a loss of about 4% of national chicken production. However, the indirect effect – consumers’ reluctance to consume poultry if AI is detected, causing a decline in chicken prices – is generally larger than the direct effect in our simulation. We estimate that Nigerian chicken production would fall by 21% and chicken farmers would lose US$250 million of revenue if the worst‐case scenario occurs. The negative impact would be unevenly distributed in the country, and some states and districts would be seriously affected. The study shows that, while most attention has focused on preventing a global influenza pandemic, preventive measures are also needed at the national, regional and local levels, because AI could potentially have a major negative impact on the poultry industry and the livelihood of smallholder farmers in many regions in West Africa.